Emotional Control in Interpersonal Communication Among Female Students at SMPN 1 Weru - Lutfi Nur Baity; Siti Khumayah; Aghnia Dian Lestari (Indonesian Journal Publisher, 2026)
The emotional development of adolescents in junior high school is very important for the quality of interpersonal communication. Adolescents’ emotional lability often has a negative effect on social interactions, emotional regulation is therefore an important factor of establishing effective relationships. This research is a descriptive study which aims to analyse the emotional regulation in interpersonal communication of female students at SMPN 1 Weru based on the Fundamental Interpersonal Relations Orientation (FIRO) theory which includes inclusion, control, and affection. This study uses a descriptive qualitative approach. The respondents of this research are seventh, eighth, and ninth grade students. Data were collected by interview, observation, and documentation, and analysed by triangulation techniques. The results indicate that students can handle emotions in interpersonal communication, but they still feel negative emotions like anxiety, fear of rejection and low self-esteem. The awareness of the needs for inclusion, control, and affection influences the quality of the social interactions of the students. Communication barriers are negative social experience and emotional instability. This study confirms the important role of emotion regulation in promoting effective interpersonal communication and contributes by integrating the concepts of emotion regulation and FIRO theory in the context of junior high school adolescents.